Referral Writer: preliminary evidence for the value of comprehensive referral letters - Jiwa, Moyez; Dhaliwal, Satvinder (Radcliffe Medical Press Ltd., 2012)
Background: We aimed to explore if increasing the amount of relevant information relayed in referral letters between general practitioners (GPs) or family physicians and hospital specialists helps in the scheduling of appointments for patients. We report a before and after study comparing outcomes before and after the introduction of software to assist referral writing. Methods: The participants were GPs and hospital specialists based in metropolitan Perth, Western Australia. The amount of relevant information in referral letters from GPs was assessed with reference to a published schedule three months before and four months after deploying interactive computerised Referral Writer software (RW). The longer period after deploying the RW was to allow GPs time to become familiar with the RW. The letters were scored by a researcher for the amount of relevant information included and then independently assessed by two specialists in each of six specialties to determine if they were able to decide which patients needed to be seen soonest and what was the most likely outcome of the specialist consultation. The actual diagnosis for each case was recorded later to assess if there was an association between the amount of relevant information relayed and the diagnosis of life limiting or other pathologies.Results: Each GP referred 5.6 patients on average, range (1, 14) before the RW and 4.8 patients, range (0, 14) after the RW. The amount of relevant information in the letters improved substantially after the RW, mean difference 37%, 95% Confidence Interval 43-30%, P <0.001. For 91% of letters after the RW, both specialists in each specialty were confident or very confident that they had enough information to decide when the patient should come to their clinic; this had increased from 50% before the RW, P = 0.001. There was no association observed between the amount of relevant information relayed and the final diagnosis. Conclusion: Standardising and using electronic communications to refer appears to facilitate rational scheduling of specialist appointments. Comprehensive referral may help to ensure that the right patients are seen by the specialist sooner rather than later.